IMPROVING STUDENTS™ SPEAKING ACHIEVEMENT IN DESCRIPTIVE TEXT BY APPLYING PICTURE IN THE SECOND GRADE OF JUNIOR HIGH SCHOOL - Nasution, Siti Handayani; -, Bachtiar (Universitas Negeri Medan, 2013)
AbstractThis research concerned with the improving students™ speaking achievement in descriptive text by applying picture in the second grade of junior high school. The objective of the research was to find out whether applying picture improves the students™ speaking achievement in descriptive text in the second grade of Junior High School. It was conducted by applying Classroom Action Research which was carried out in two cycles in six meetings. The subject of this research was the second grade students™ class VIII of SMP Negeri 1 Kisaran which consisted of 36 students. The instrument for collecting data were speaking test, observation sheet, interview, and diary notes. The techniques for data analysis were quantitative and qualitative data. In analyzing data, the mean for the students™ score in orientation test was 57.16, for the cycle I test was 68.63, and for the cycle II test was 79 and total percentage of the studentswho got improvement from the orientation test up to cycle II test was 85.72. The result of this research showed that by applying picture significantly improved students™ speaking achievement in descriptive text.Keywords: Descriptive Text, Picture, Students™ Speaking Achievement